PENGESAMPINGAN PERSAMAAN PADA POKOKNYA DALAM PENDAFTARAN MEREK OLEH PRINSIP "FIRST TO FILE" - Farah Anisah Zahran (2021)
Article 3 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications states the Right to a Mark is obtained after the mark is registered. This article provides a statement that the legal protection of trademarks is based on the "first to file" principle, namely the first registrant. This study aims to examine the principle of "first to file" dealing with the Similarity in Essence in the Supreme Court Decision Number 576 K/Pdt.SUS-HKI/2020, the case between Ruben Onsu and Yangcent regarding the "BENSU" brand rights. How "first to file" overrides the Similarity in Essence on a registered marks and how the Judge's judgement on the registered mark relates to the Similarity in Essence. The research was using Normative Juridical through a statute approach and a case approach. It's expected to provide benefits especially for those who have a trademark but haven't yet registered to register their trademark to get legal protections.